2016
DOI: 10.1002/asi.23721
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and tracing the outcomes and impact of research infrastructures

Abstract: Recent policy shifts on the part of funding agencies and journal publishers are causing changes in the acknowledgment and citation behaviors of scholars. A growing emphasis on open science and reproducibility is changing how authors cite and acknowledge "research infrastructures"-entities that are used as inputs to or as underlying foundations for scholarly research, including data sets, software packages, computational models, observational platforms, and computing facilities. At the same time, stakeholder in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 123 publications
(155 reference statements)
0
49
0
2
Order By: Relevance
“…In an extensive review of research efforts similar to the Oklahoma Mesonet pilot project described here, Mayernik et al (2017Mayernik et al ( : 1354 have suggested that practical, in-depth studies of specific 'research infrastructures' that routinely provide significant research assets, such as datasets and datastreams, also offer unique Utilization (Kenkel & Norris 1995: 365) The two objectives of the study were to estimate average willingness to pay and to determine the characteristics of producers who would pay to access and use mesoscale weather information. To this end, two maximum likelihood models were estimated: one for the raw [Oklahoma] Mesonet data and one for the raw data/value-added information combination .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an extensive review of research efforts similar to the Oklahoma Mesonet pilot project described here, Mayernik et al (2017Mayernik et al ( : 1354 have suggested that practical, in-depth studies of specific 'research infrastructures' that routinely provide significant research assets, such as datasets and datastreams, also offer unique Utilization (Kenkel & Norris 1995: 365) The two objectives of the study were to estimate average willingness to pay and to determine the characteristics of producers who would pay to access and use mesoscale weather information. To this end, two maximum likelihood models were estimated: one for the raw [Oklahoma] Mesonet data and one for the raw data/value-added information combination .…”
Section: Resultsmentioning
confidence: 99%
“…Although the Oklahoma Mesonet has been routinely compiling a bibliography of publications pertinent to its efforts since its inception, the study described here is an initial attempt toward a formal analysis of the peerreviewed scientific publications, their uses of the Oklahoma Mesonet data, and toward further efforts to understand and facilitate such Mesonet data usage. Mayernik et al (2017Mayernik et al ( : 1344 assert that 'Manual processes for collecting publications that cite data sets . .…”
Section: Methodsology: Oklahoma Mesonet Sensor Data Publication Analysismentioning
confidence: 99%
“…5. Data impact: Citing data allows us to define new usage metrics for determining the impact of data; data impact can be interpreted as a way to measure or discover which results have been obtained using the data, how many (2011) Bioinformatics Kafkas, et al (2015) Biomedicine King (1995) Information Studies Klump, et al (2016) Earth Science Koers (2015) Clinical Epidemiology Mayernik (2012) Information Studies (Mayernik, et al, 2017) Information Studies Mooney and Newton (2012) Data Publishing Nature Physics Editorial (2016) Physics Parson (2012) Earth Science Parsons and Fox (2013) Data Publishing Peters et al (2016) Information Studies Pr€ oll and Rauber (2013) Computer Science Sieber and Trumbo (1995) Information Studies Silvello and Ferro (2016) Digital Libraries Silvello (2015) Information Retrieval Silvello (2017) Computer Science Simons, Visser, and Searle, (2013) Digital Libraries Starr et al (2015) Computer Science Thorisson (2009) Biotechnology White (1982 Social Sciences Wormack (2015) Information Studies Zw€ olf et al (2016) Spectroscopy times they have been used, where they have been used, and so on. Note that in the literature, data impact is, frequently, intended as the rate of data usage and not as a quality measure.…”
Section: Why Data Citation: Motivationsmentioning
confidence: 99%
“…This is also due to the fact that data citations "are useful for the discovery of links, but less so for understanding why the link was made" . Mayernik et al (2017Mayernik et al ( , p. 1354 are among the few hypothesizing that data may be cited as "forms of reward to data providers," as a "quid pro quo for the data provider support," or as a "persuasive statement illustrating how data of high visibility or sufficient quality underlie a scientific result." Up to now, we can only find isolated and sporadic efforts to understand why data are cited.…”
Section: Why Data Citation: Motivationsmentioning
confidence: 99%
“…We use the term “research infrastructures” as an overarching grouping of multiple kinds of resources, building on terminology established in international contexts [20,21]. “Research infrastructures” include scientific equipment, collections and archives of scientific data or software, computing systems, and any other tools that enable research.…”
Section: Background: From Data Citation To Research Infrastructure CImentioning
confidence: 99%